Participant Adherence Indicators Predict Changes in Blood Pressure, Anthropometric Measures, and Self-Reported Physical Activity in a Lifestyle Intervention: HUB City Steps - Thomson, Jessica L. (Health Educ Behav, 2014)
The objective of this secondary analysis was to evaluate the utility of several participant adherence indicators for predicting changes in clinical, anthropometric, dietary, fitness, and physical activity (PA) outcomes in a lifestyle intervention, HUB City Steps, conducted in a southern, African American cohort in 2010. HUB City Steps was a 6 month, community engaged, multi component, non controlled, intervention targeting hypertension risk factors. Descriptive indicators were constructed using 2 participant adherence measures, education session attendance (ESA) and weekly steps/day pedometer diary submission (PDS), separately and in combination. Analyses, based on data from 269 primarily African American adult participants, included bivariate tests of association and multivariable linear regression to determine significant relationships between 7 adherence indicators and health outcome changes, including clinical, anthropometric, dietary, fitness, and PA measures. ESA indicators were significantly correlated with 4 health outcomes, body mass index (BMI), fat mass, low density lipoprotein (LDL), and PA ( .29≤ r ≤ .23; P<.05). PDS indicators were significantly correlated with PA (r=.27; P<.001). Combination ESA/PDS indicators were significantly correlated with 5 health outcomes, BMI, % body fat (%BF), fat mass, LDL, and PA (r= .26 to .29; P<.05). Results from the multivariate models indicated that the combination ESA/PDS indicators were the most significant predictors of changes for 5 outcomes, %BF, fat mass, LDL diastolic blood pressure (DBP), and PA, while ESA performed best for BMI only. For DBP, a 1 unit increase in the continuous categorical ESA/PDS indicator resulted in .3 mm Hg decrease. Implications for assessing participant adherence in community based, multi component lifestyle intervention research are discussed.